Reorientation Of Mayor Regulation Number 28 Of 2024 For Taxpayers In Medan City - Bayu Widianto; Chely Br Sembiring; Hendri Yohannes (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The principle of legal certainty and legality of tax collection is an important principle in a state of law as stated in the 1945 Constitution that Indonesia is a state of law and a tax cannot be collected without being regulated by law. The Mayor's Regulation is an implementing regulation that has binding legal force which is ordered by higher legislation or formed based on authority. The position of the Medan Mayor's Regulation Number 28 of 2024 raises a legal event. This study will critically examine and analyze, and normatively regarding the Mayor's Regulation based on the perspective of comparative law theory both from the decision of the constitutional court, the formation of regional legal products and relevant laws and enforcing the law in implementing it for taxpayers. This study aims to determine whether the formation of the Mayor's Regulation is in accordance with the authority and ordered by the Legislation and the validity of the law in implementing the Mayor's Regulation. The results of the study found that the Mayor's Regulation is an implementing regulation that does not have the authority to add non-normative substance, the Mayor's Regulation only has the authority to regulate administrative procedures. Officials who should not implement the Mayor's Regulation, if it conflicts with higher regulations based on the principle of lex superior derogat legi inferiori, in carrying out their duties and responsibilities must comply with the Laws and Regulations